Skeletal growth and the changing genetic landscape during childhood and adulthood - Duren, Dana L.; Seselj, Maja; Froehle, Andrew W.; Nahhas, Ramzi W.; Sherwood, Richard J. (American journal of physical anthropology, 2013)
Growth, development, and decline of the human skeleton are of central importance to physical anthropology. All processes of skeletal growth (longitudinal growth as well as gains and losses of bone mass) are subjected to environmental and genetic influences. These influences, and their relative contributions to the phenotype, can be asserted at any stage of life. We present here the gross phenotypic and genetic landscapes of four skeletal traits, and show how they vary across the life span. Phenotypic sex differences are found in bone diameter and cortical index (a ratio of cortical thickness over bone diameter) at a very early age and continue throughout most of life. Sexual dimorphism in summed cortical thickness and bone length, however, is not evident until shortly after the pubertal growth spurt. Genetic contributions (heritability) to these skeletal phenotypes are generally moderate to high. Bone length and bone diameter (which both scale with body size) tend to have the highest heritability, with heritability of bone length fairly stable across ages (with a notable dip in early childhood) and that of bone diameter peaking in early childhood. The bone traits summed cortical thickness and cortical index that may better reflect bone mass, a more plastic phenomenon, have slightly lower genetic influences, on average. Results from our phenotypic and genetic landscapes serve three key purposes: 1) demonstration of the integrated nature of the genetic and environmental underpinnings of skeletal form, 2) identification of periods of bone's relative sensitivity to genetic and environmental influences, 3) and stimulation of hypotheses predicting the effects of exposure to environmental variables on the skeleton, given variation in the underlying genetic architecture. Am J Phys Anthropol, 2013. © 2012 Wiley Periodicals, Inc.